Childhood vascular phenotypes have differing associations with prenatal and postnatal growth. Issue 9 (September 2021) - Sletner, Line; Crozier, Sarah R.; Inskip, Hazel M.; Godfrey, Keith M.; Mahon, Pamela; Chiesa, Scott T.; Charakida, Marietta; Cooper, Cyrus; Hanson, Mark
Abstract : Objective: In children aged 8–9 years, we examined the associations of linear and abdominal circumference growth during critical stages of prenatal and postnatal development with six vascular measurements commonly used as early markers of atherosclerosis and later cardiovascular disease (CVD) risk. Methods: In 724 children from the UK Southampton Women's Survey mother–offspring cohort, offspring length/height and abdominal circumference measurements were collected at 10 ages between 11 weeks' gestation and age 8–9 years. Using residual growth modelling and linear regression, we examined the independent associations between growth and detailed vascular measures made at 8–9 years. Results: Postnatal linear and abdominal circumference growth were associated with higher childhood SBP and carotid–femoral pulse wave velocity, whereas prenatal growth was not. For example, 1SD faster abdominal circumference gain between ages 3 and 6 years was associated with 2.27 [95% confidence interval (CI): 1.56–2.98] mmHg higher SBP. In contrast, faster abdominal circumference gain before 19 weeks' gestation was associated with greater carotid intima–media thickness [0.009 mm (0.004–0.015) per 1SD larger 19-week abdominal circumference), whereas later growth was not. We found no strong associations between prenatal or postnatal growth and DBP or measures of endothelial function. Conclusion: Higher postnatal linear growth and adiposity gain are related to higher SBP and carotid–femoral pulse wave velocity in childhood. In contrast, faster growth in early gestation is associated with greater childhood carotid intima–media thickness, perhaps resulting from subtle changes in vascular structure that reflect physiological adaptations rather than subclinical atherosclerosis. Abstract : Supplemental Digital Content is available in the text